Keanekaragaman dan Peranan Serangga Pengunjung Pada Tanaman Kacang Panjang di Kecamatan Kerkap Kabupaten Bengkulu Utara Provinsi Bengkulu - Endang Sulaiman; Pariyanto Pariyanto; Apriza Fitriani; Yuni Puspita (bionature, 2022)
This study aims to determine the Diversity and Role of Visitor Insects on Long Bean Plants in Kerkap District, North Bengkulu Regency. The location of this research is in 4 villages in Kerkap District, North Bengkulu Regency. This study uses a direct survey method to the research location which has been carried out in January – February 2022. The method used in this study is a survey method directly to the field while the sampling of insects is by purposive sampling. Based on the results of research that has been carried out on a long bean plantation (Vigna sinensis.L) in Kerkap District, North Bengkulu Regency, it was found that insects belong to 6 orders, 16 families and 26 species. The diversity was to index of visitor insects to obtained from 4 villages in Kerkap District that was categorized as moderate, namely (H') = 1.084. The results of measurements were of ecological factors in long bean plantations in Kerkap District, North Bengkulu Regency that ranged from 28ºC - 37ºC, air humidity ranged from 46% - 69% and light intensity ranged from 1105 Lux - 2846 Lux.